Effect of water stress on herbicide efficiency applied to Urochloa decumbens - Rocha-Pereira, Maria R. [UNESP] (2012)
M.R. Rocha-Pereira, A.E. Klar, D. Martins, G.S. Ferreira de Souza, and J. Villalba. 2012. Effect of water stress on herbicide efficiency applied to Urochloa decumbens. Cien. Inv. Agr. 39(1): 211-220. This project aimed to measure the control efficiency of Acctil Coenzime A Carboxilase (ACCase)-inhibiting herbicides post-emergence applied to Urochloa decumbens (Stapf) R.D. Webster under different soil water contents. The experiment was conducted in a greenhouse at the Department of Plant Production, Faculty of Agronomic Sciences, UNESP, Botucatu, Silo Paulo. The experimental design was a completely randomized design with four replications, consisting of a 9 x 4 factorial, combined with three water management systems (-0.03, -0.07 and -1.5 MPa) and three herbicides (fluazifop-p-butyl, haloxyfop-methyl and sethoxydim + oil using four doses (100, 50, 25 and 0% of the recommended dose). Herbicide applications were conducted at two vegetative stages for all species: a 4-6 leaf stage and a 2-3 tiller stage. The physiological parameters evaluated were as follows: photosynthetic rate, stomatal conductance, transpiration, leaf temperature and plant dry matter. The visual assessments of phytotoxicity were performed 28 days after herbicide application. The control efficiency was lower in plants grown under soil water potential conditions of -1.5 MPa, regardless of the herbicide used during the two application stages; however, none reached 100% control. Fractionation of the recommended herbicide doses reduced effectiveness, with the exception of the 50%-dose application of sethoxydim and fluazifop-p-butyl herbicides, which were also effective in the 4-6 leaf plant control under normal water conditions.